Risiko Konsumsi Western Fast Food dan Kebiasaan Tidak Makan Pagi Terhadap Obesitas Remaja Studi di SMAN 1 Cirebon - Lilis Banowati; Nugraheni Nugraheni; Niken Puruhita (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTRisks of western fast food consumption and skipping breakfast to adolescents’obesity: Study at SMAN 1 CirebonBackground: Obesity prevalence in adolescents remains high. Western fast food consumption and skipping breakfast were identified as sub-culture among adolescents.The objective of this study was aimed to determine the risk of western fast food consumption in term of frequency of consumption, energy intake and energy contribution to adolescents’ obesity. It was also aimed to determine therisk of skipping breakfast for adolescents’ obesity.Method: It was an observational study using a case-control approach. Stratified random sampling was used to select participants from population. Seventy six secondary students from SMA Negeri 1 Cirebon were involved, divided into two groups; 38 students as case (BMI>95 persentile) and the rest 38 as controls (BMI 5-85 persentile). Chi-square and multiple logistic regression were employed in data analysis.Results: This study found obese students consumed western fast food more than their counterparts (263 kkal versus 140 kkal) (p=0.001). They were less frequent breakfast having (4.5 times per week) than those who were not obese (5,8 times per week) (p=0.019). Energy intake gained from western fast food consumption ≥244 kkal per day was found as the risk factor for obesity among adolescents (p=0,004) whilst frequency of consumption >9.2 times per month, energy contribution to total calorie intake >7.3% and skipping breakfast were failed to predict adolescents’ obesity (p>0.05). The result of multiple logistic regression test showed that the variable which is the most influential to the incident of obesity is energy intake gained from western fast food consumption (OR=6.26).Conclusion: Western fast food consumption ≥244 kkal per day is a risk factor for obesity.Keywords: Western fast food consumption, skipping breakfast, obesity, adolescentABSTRAKLatar belakang: Prevalensi obesitas remaja cukup tinggi. Hal ini disebabkan oleh konsumsi western fast food dan kebiasaan tidak makan pagi yang sudah merupakan kecenderungan di kalangan remaja. Tujuan penelitian ini untuk mengetahui besar risiko frekuensi konsumsi western fast food, asupan energi konsumsi western fast food, kontribusi energi western fast food dan kebiasaantidak makan pagi terhadap kejadian obesitas remaja SMAN 1 Cirebon.Metode: Jenis penelitian observasional dengan rancangan kasus kontrol. Pengambilan sampel dengan teknik stratified random sampling. Besar sampel 76 orang, terdiri dari 38 orang kasus (IMT >95 persentil) dan 38 orang kontrol (IMT persentil ke-5 -85). Penelitian menggunakan analisis bivariat dengan uji chi square dan analisis multivariat dengan uji regresi logistik ganda.Hasil: Pada remaja obesitas asupan energi konsumsi western fast food (263 kkal) lebih tinggi daripada yang tidak obes (140 kkal) (p=0,001). Sedangkan frekuensi makan pagi lebih rendah (4,5 kali/minggu) daripada yang tidak obes (5,8 kali/minggu) (p=0,019). Hasil analisis menunjukkan asupan energi konsumsi western fast food ≥244 kkal per hari merupakan faktor risiko terjadinyaobesitas (p=0,004). Sedangkan frekuensi konsumsi western fast food >9,2 kali per bulan, kontribusi energi western fast food terhadap total kalori >7,3% dan kebiasaan tidak makan pagi bukan faktor risiko obesitas (p>0,05). Hasil uji regresi logistik ganda menunjukkan bahwa variabel yang paling berpengaruh terhadap obesitas remaja adalah asupan energi konsumsi western fast food(OR=6,26).Simpulan: Konsumsi western fast food ≥244 kkal per hari berisiko untuk terjadinya obesitas.